2010
DOI: 10.1051/alr/2010018
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture system diversity and sustainable development: fish farms and their representation

Abstract: -Initiatives for the sustainable development of aquaculture have so far focused on the production of codes of conduct, of best management practices, of standards etc., most of which have been developed by international organisations, the industrial sector and non governmental organisations. They were, to a large extent, produced using a "top down" process and inspired by models from intensive industrial shrimp and sea fish farming (mainly salmon). However, most of global aquaculture production comes from small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Therefore, it reflects the activity's importance to the economy and community of a territory. For instance, one tonne of fish from Pampanga polyculture requires onsite human labour of 74 man.day (52% of total human labour), compared to on-site labour of 13 man.day for trout farming in France (unpublished data), an intensive system poorly integrated with the community of the territory it occupies (Lazard et al, 2010). To better understand the direct and indirect influence of the activity on the value chain, it is necessary to complement attributional LCA with other methods, such as the Porter Value Chain or Life Cycle Costing .…”
Section: Other Environmental Impactsmentioning
confidence: 99%
“…Therefore, it reflects the activity's importance to the economy and community of a territory. For instance, one tonne of fish from Pampanga polyculture requires onsite human labour of 74 man.day (52% of total human labour), compared to on-site labour of 13 man.day for trout farming in France (unpublished data), an intensive system poorly integrated with the community of the territory it occupies (Lazard et al, 2010). To better understand the direct and indirect influence of the activity on the value chain, it is necessary to complement attributional LCA with other methods, such as the Porter Value Chain or Life Cycle Costing .…”
Section: Other Environmental Impactsmentioning
confidence: 99%
“…However, in this study, we define "small scale" for ponds area ranges from 1000 to 2800 m 2 . Those fall in this category could be considered vulnerable, referred to the fact that they are characterized by limited capital, limited access to technology and limited access to the market, and these characters are found in small scale aquaculture activities in many countries (Lazard et al, 2010;Anonymous, 2013).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…3,199 trillion worth of products work out their own difficulties? Aquaculture community's important role in attaining food security is acknowledged, not only locally but also globally, and the fact that most of the contributors are small medium sized farms (Lazard et al, 2010), focus towards establishing resilient fish farming community is imperative.…”
Section: Reorganize and Institutionalize The Learning And Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Typologies carried out by area (Lazard et al 2009(Lazard et al , 2010 revealed quite a large diversity in production and regulatory systems. Leaving aside the Tangkit site (Indonesia) where aquaculture systems are very homogeneous, three or four different farm types were identified in each area, regardless of whether or not there was a large number of farms.…”
Section: Territorial Diagnoses Of Aquaculture System Sustainabilitymentioning
confidence: 99%